FROM THE ARCHIVE OF “FAZIL-I FENA FİL EVKAF” SEPULCHRAL MONUMENTS OF CALLIGRAPHIST - ÖZGEN, Mutlu (Atlas Journal, 2018)
The way made İsmail Fazıl Ayanoğlu important in terms of Foundations and our cultural history is that he has a rich photograph archieve taken by him once upon a time and classified by their subjects and described by him as "Evidents of a small part of the civilization ocean". From this aspect, Ayanoğlu is known as also “fazıl-ı fena filevkaf” in the General Directorate of Foundations in Istanbul had served for General Directorate of Foundations until the date of his death is a founder and a man of culture, who participated in the operations for issuing, moving of the foundation cemeteries (in the grave transfer operations), reading epigraphs, renew and classification of them as a specialist of ancient artworks and sepulchral monuments in the General Directorate of Foundations in Istanbul for many years and undertaken an active role for taking photographs of many ancient artworks, particularly sepulchral monuments and recorded and brought to the future. After his death, Ayanoğlu has continued to contribute to scientific works of investigtors with his own books in the İbrahim Hakkı Konyalı Library and very rich photograph archive of ancient works and to provided visual support to the works of many investigators. In this study some sepulchral monument photographs of Calligraphists, considered as one of the the most important samples of photograph archive of İsmail Fazıl Ayanoğlu, are protcted in the file numbered 5403 in the archieve department of the İbrahim Hakkı Konyalı Library and previously never published anywhere, general view and biographic contents of epigraphs shall be included in chronological order.